EFFORTS TO INCREASE ABILITY TO MAKE SOLUTIONS OF MATHEMATICAL STORIES THROUGH DISCOVERY LEARNING MODEL ON ELEMENTARY SCHOOL STUDENTS - Ratnaningsih, Sita; Carera, Ressa; Fatra, Maifalinda (JMIE (Journal of Madrasah Ibtidaiyah Education), 2017)
This study to improve the ability to solve word mathÂ  through discovery learning model in the elementary school students. This research method using Classroom Action Research method. The result showed that studentsâ€™ ability to solve word problems through a model of discovery learning has increased. Increase students ability to solve word problems can be seen in the first cycle obtained 68,6 and an average increase incycle II to 83,5. Incerased ability to sove word problem are also characterized by increased activity of the students, the average of the first cycle of 70,8% of the student activity increased by 15,7% in the second cycle becomes 86,5%. The positive response of student towards learning discovery learning model in the first 71,2%, also an increase of 13,5% from 84,7% in the first cycle to second cycle.